Resveratrol biotechnological applications: enlightening its antimicrobial and antioxidant properties - Sharifi-Rad, Javad (2022)
Introduction Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a polyphenol obtained from diverse groups of plants, especially in the muscadine grape, red wine, lingonberry, cranberry and redcurrant. Resveratrol's health benefits were first highlighted in the study of the French paradox, which opened up an expansive research endeavor into this compound. Ever since, an array of pharmacological activities, including antioxidant, antiaging, anti-inflammatory, anti-cancer and antidiabetic have been attributed to resveratrol. For many polyphenols, low solubility in biological fluids, as well as by rapid in vivo metabolization, limits their bioavailability. However, improving resveratrol formulation could enhance oral bioavailability and have other beneficial properties. The development of innovative methodological approaches, such as the utilization of innovative formulations has been developed to overcome these limitations and provide a considerable therapeutic amount of resveratrol. Results In this narrative review, a brief outline of historical perspectives of resveratrol is provided, together with an extensive and inclusive overview of various approaches and contemporary developments on the bioavailability, pharmacodynamics and pharmacokinetics of this nutraceutical, along with its biotechnological applications and drug formulations.